Residual breast tissue after robot-assisted nipple sparing mastectomy. (February 2021) - Park, Ko Un; Tozbikian, Gary H.; Ferry, David; Tsung, Allan; Chetta, Mathew; Schulz, Steven; Skoracki, Roman
Abstract: Introduction: While the long-term oncologic safety of robot-assisted nipple sparing mastectomy (RNSM) remains to be elucidated, histologically detected residual breast tissue (RBT) can be a surrogate for oncologically sound mastectomy. The objective of this study is to determine the presence of RBT after RNSM. Methods: Between August 2019–January 2020, we completed 5 cadaveric RNSMs. Full thickness biopsies from the mastectomy skin flap were obtained from predefined locations radially around the mastectomy skin envelop and nipple areolar complex to histologically evaluate for RBT. Results: The first case was not technically feasible due to inability to obtain adequate insufflation. Five mastectomy flaps were analyzable. The average mastectomy flap thickness was 2.3 mm (range 2–3 mm) and the average specimen weight was 382.72 g (range 146.9–558.3 g). Of 70 total biopsies, RBT was detected in 11 (15.7%) biopsies. Most common location for RBT was in the nipple-areolar complex, with no RBT detected from the peripheral skin flaps. Conclusions: In this cadaveric study, RNSM is feasible leaving minimal RBT on the mastectomy flap. The most common location for RBT is in the periareolar location consistent with previous published findings after open NSM. Clinical studies are underway to evaluate the safety of RNSM. Highlights: Robot-assisted nipple sparing mastectomy (RNSM) is technically feasible. Residual breast tissue after RNSM is histologically detected only from the periareolar location. Further clinical trials are underway to determine oncologic safety of RNSM.